Advances in human factors in robots, drones and unmanned systems : proceedings of the AHFE 2020 Virtual Conference on Human Factors in Robots, Drones and Unmanned Systems, July 16-20, 2020, USA /: proceedings of the AHFE 2020 Virtual Conference on Human Factors in Robots, Drones and Unmanned Systems, July 16-20, 2020, USA. (2020) - Unknown
No abstract available